Analisis Hadis 'Arrāf dan Fenomena Ramalan Zodiak di TikTok: Studi Ma'anil Hadis Perspektif Hermeneutika Yusuf Al-Qardhawi - Putri Melinda Rahmawati; Nur Efendi; Kojin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
The rapid transformation of digital media has reshaped religious behavior, particularly through the normalization of zodiac prediction content on TikTok, which is often dismissed as mere content despite serious theological implications. This study responds to the phenomenon of digital fortune telling by reinterpreting the prophetic tradition regarding ‘arraf (fortune tellers) within a modern hermeneutical framework. This study aims to examine the Science of Ma’anil Hadith (Hadith Hermeneutics) from the perspective of Yusuf Al-Qardhawi and to analyze the contemporary relevance of the hadith in Ṣahih Muslim No. 2230 from that perspective. Using a qualitative research method, a type of library research, strengthened by digital observation of the hashtag #zodiacpredictions with a minimum of 80,000 views. The results show that the classic concept of “visiting” (atā) a fortune teller in this hadith has mutated into digital engagement, such as watching, liking, and validating content through comments like “relate or yes, this is absolutely true!” Through the four methodologies of Ma'anil Hadith Al-Qardhawi, which include harmonization with the Qur'an, collection of hadith on the same theme, understanding the historical context (asbabul wurud), and synchronization between narrations, this study concludes that interacting with zodiac content triggers spiritual consequences in the form of non-acceptance of prayers for forty nights, while believing in the predictions can lead to disbelief.